Study of the ψ2(3823) and χc1(3872) states in B+ → (J/ψπ+π-) K+ decays - Aaij, Roel; Archilli, Flavio; Bachmann, Sebastian; Berninghoff, Daniel; Borsato, Martino; Braun, Svende; Dziewiecki, Michal; Frau, Giulia; Gerick, David; Grabowski, Jascha; Han, Xiaoxue; Hansmann-Menzemer, Stephanie; et al. (Journal of high energy physics, 2020)
The decays B+ → J/ψπ+π−K+ are studied using a data set corresponding to an integrated luminosity of 9 fb−1 collected with the LHCb detector in proton-proton collisions between 2011 and 2018. Precise measurements of the ratios of branching fractions with the intermediate ψ2(3823), χc1(3872) and ψ(2S) states are reported.